KANUNISASI FIKIH JINAYAT KONTEMPORER Studi Materi Muatan QÄnÅ«n JinÄyat Aceh dan Brunei Darussalam - Aziz, Samsudin (Al-Ahkam, 2014)
This article will view specifically codification of Islamic Criminal Law in `Muslim community, such as Brunei Darussalam, a country based on Islamic principles, and Aceh is a part of Indonesian territory administratively, granted special autonomy to implement Islamic Sharia. Despite having different qualities, -as a country and a province- both have in common as a political power which apply Islamic Criminal Law. Refer to both qÄnÅ«n jinÄyat in Brunei and Aceh, the authorâ€™ll explain the substance of the criminal law in both area, while also reinforces the implementation of Islamic Criminal Law in the framework of a modern state. The article concludes that basically the application of Islamic Sharia, particularly the Islamic Criminal Law, is closely related to the situation and socio-political conditions of a community or country. The differences of political system, for example, has contributed to the difference in the output of product or policy made by a particular country or territory. On the other hand, Brunei and the Aceh case show that there has been adjustment Islamic Criminal Law specifically set forth in the books of fiqh (as illustration of the Qur'an and Sunnah) with the needs of the community itself